Youth digital health and online platforms - Gliniecka, Martyna, author.
1 online resource.
Keywords: "Youth Digital Health and Online Platforms focuses on young people's use of the digital platform Reddit for health. Drawing upon dialogism theory, the book explores how young people produce a youth-led discourse of youth digital health, different from the adult-led framing represented in youth digital health research, policy, and service delivery. Peer-led discussions online remain one of the controversial forms of youth digital health, associated with negative peer influence or casual 'teenage talk'. This book argues that online peer-led dialogues support young people's agency in health and that young people can benefit from dealing with health issues with peers. This work is based on the digital ethnography of teenagers' subreddits on Reddit, and utilises a theoretical framework of dialogism, a linguistic-based theory originatedy by an early 20th-century Russian philosopher, Mikhail Bakhtin. The book introduces the concept of dialogical youth-led youth digital health discourse formed in the peer-led space of Reddit. This youth-led discourse celebrates equality and diversity amongst people, meanings, and opinions. It is constructed around three relational elements: socio-material affordances, creative practices, and a plurality of youth voices. Reddit's pseudonymous, anti-authoritarian, and egalitarian nature supports the emergence of this youth-led discourse. The book can interest scholars and lecturers in childhood and youth studies, Internet studies, and youth health studies. Professionals such as policymakers, service designers/deliverers, online safety educators, and global youth and health agencies can use evidence-based insights in their work with young people"--